The impact of recordings of police actions on organizational culture - Lehel Hunor András; Gábor Bélai (Belügyi Szemle)
Aim: The Communications Service of the National Police Headquarters informed the media that body cameras were being tested by the police. The introduction of police body cameras is not only a technological innovation, but also a change that can significantly affect the organisational culture of law enforcement agencies. For this reason, the authors decided to examine the effect of camera footage in shaping the organisational culture of the police. In this study, the authors approach the practice of showing recordings from a sociological point of view, presenting both its advantages and disadvantages.